TRANSFORMASI MITRA DAKWAH TENTANG STRATEGI DAKWAH DALAM PERSPEKTIF IBADAH - Mohammad Niamulloh (Jurnal Dakwah Tabligh, 2020)
This paper aims to determine the characteristics of mad'u (da'wah partners) and how to deliver it so that it is conveyed properly to mad'u. The results of this journal are as follows: 1) grouping the characteristics of mad'u into 3 (three): a) abangan, b) santri and c) priayi. 2) knowing the material presented includes a) (Original from Allah SWT), b) Easy and good, c) Balanced, d) Complete and Universal, e) Makes sense. Broadly speaking, the delivery of dakwah cannot be equated, meaning that the delivery varies depending on the level of the dakwah partner. Before preaching is conveyed, it is necessary to have specifications so that the objectives of da'wah can be achieved and can be effective. Da'wah itself is an intermediary for the development of Islam, this is the initial framework in forming a good and effective da'wah paradigm.